2013
DOI: 10.1093/hmg/ddt042
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of Neuron-derived Orphan Receptor-1 (NOR-1) exacerbates neointimal hyperplasia after vascular injury

Abstract: We have previously shown that NOR-1 (NR4A3) modulates the proliferation and survival of vascular cells in culture. However, in genetically modified animal models, somewhat conflicting results have been reported concerning the involvement of NOR-1 in neointimal formation after vascular injury. The aim of this study was to generate a transgenic mouse model over-expressing NOR-1 in smooth muscle cells (SMCs) and assess the consequence of a gain of function of this receptor on intimal hyperplasia after vascular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 41 publications
3
62
0
1
Order By: Relevance
“…Permanent ligation of the left common carotid artery was performed as previously described 20,41 . Four-month-old mice were distributed into four groups: WT (n = 12), WT mice receiving BAPN (100 mg/kg/day; ip; n = 7) from the day before surgical intervention and throughout the experimental procedure, TgLOX (n = 10) and TgLOX treated with BAPN (n = 6).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Permanent ligation of the left common carotid artery was performed as previously described 20,41 . Four-month-old mice were distributed into four groups: WT (n = 12), WT mice receiving BAPN (100 mg/kg/day; ip; n = 7) from the day before surgical intervention and throughout the experimental procedure, TgLOX (n = 10) and TgLOX treated with BAPN (n = 6).…”
Section: Methodsmentioning
confidence: 99%
“…After 3 weeks under standard chow diet the animals were anaesthetized with ketamine (75 mg/kg) and medetomidine (1 mg/kg) and sacrificed by thoracotomy. Carotid arteries were then excised, fixed in 4% paraformaldehyde/0.1 M PBS (pH 7.4) for 24 h, and embedded in paraffin for morphometric and immunohistochemical analysis 41 . Serial sections (5 µm thick) of paraffin-embedded arteries were cut using a microtome (Leica JUNG RM 2055).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas Nur77 has been reported to mediate the pro-inflammatory response in macrophages via the NFkB pathway [16] by activating the inducible kinase IKKi [17], other studies reported that, similar as Nurr1, Nur77 may also exert anti-inflammatory effects in macrophages [15]. NOR1 has been suggested to be pro-atherogenic since it promotes human and murine VSMC and EC proliferation [18,19] and induces the expression of VCAM-1 and ICAM-1 in EC thus enhancing monocyte adhesion [20]. Moreover, macrophage NOR1 seems to play a protective role in atherogenesis, since it inhibits the inflammatory response of macrophages as well as their ability to transform into foam-cells [15].…”
Section: Introductionmentioning
confidence: 99%